Cutaneous pancreatic metastasis: A case report and review of literature - Abdel Hafez H (Wolters Kluwer Medknow Publications, 2008)
Pancreatic cancer is one of the most dangerous human cancers and will continue to be a major unsolved health problem as we enter the 21 st century. This is the case despite advances in imaging technology and surgical management. Indeed, 80% to 90% of pancreatic cancers are diagnosed either at the locally advanced or metastatic stage. Cutaneous metastases originating from pancreatic cancer are relatively rare. The most common site of cutaneous metastasis is the umbilicus, and this is known as the Sister Joseph′s nodule. Very few patients have been reported with cutaneous lesions disclosing a pancreatic carcinoma at sites other than the umbilical area. To the best of our knowledge, there have been no previous reports on cutaneous pancreatic metastasis in Egypt. This is a report on a patient with cutaneous pancreatic metastases at the neck and review of reported non-umbilical cutaneous metastases from pancreatic carcinoma in the literatures.